Factores asociados a la deserción del curso virtual «Evaluación, Calificación y Certificación de la Persona con Discapacidad» en Perú - Perales Salazar, Judith (2024)
Objective: To determine the factors associated with desertion in a virtual course on disability developed in Peru. Materials and methods: A descriptive, cross-sectional and analytical study was carried out on physicians between 28 and 60 years of age working in different regions of Peru who participated in a virtual course organized in a National Rehabilitation Institute. Sociodemographic variables, factors that functioned as challenges and obstacles, and factors that functioned as support and satisfaction for attrition were evaluated. Results: 229 physicians participated, of whom 32 were dropouts and 197 were non-dropouts (115 men and 114 women), with an average age of 35 years. A statistically significant difference was found between the dropout and non-dropout groups in relation to age, health subsector, and marital status. Factors associated with attrition in the virtual course were age for the 36-43 group (probabilistic risk assessment [PRa]: 1.15; 95% CI: 1.04-11.60) and 44-51 (PRa: 1.19; 95% CI: 1.01-1.40), ESSALUD subsector (PRa: 1.34; 95% CI: 1.09-1.64) and working in the Armed Forces Health Services (PRa: 1.47; 95% CI: 1.10-1.93), and marital status “other” (PRa: 1.31; 95% CI: 1.08-1.57). Conclusions: There is a high frequency of attrition from the virtual course in the age groups 36 to 51, EsSalud subsector and marital status “other” amongst participants. When considering associated factors, there is a high frequency of attrition from the virtual course due to work overload and connectivity problems.